Volume Loss Caused By Tunnelling In Kenny Hill Formation - Khoo, C.-M. (GEOMATE International Society, 2019)
The Klang Valley MRT Sungai Buloh â Kajang (SBK) Line, Malaysiaâs first mass rapid transit line involved the construction of 9.5km twin bored tunnels in the densely populated urban area of Kuala Lumpur city. The underlying geological conditions can be distinctly demarcated to two main formations namely Kuala Lumpur Limestone and Kenny Hill Formation, of which 5.262km of bored tunneling was carried out in the Kenny Hill Formation. The bored tunnel construction in the Kenny Hill Formation was undertaken with the use of Earth Pressure Balance (EPB) Tunnel Boring Machine (TBM). The ground settlement due to tunneling is largely dependent on the volume loss induced by the tunnel excavation. At present, little information has been published on actual volume loss encountered during tunnel construction in the various soil types in Malaysia. Surface settlement markers among other instruments that were placed at selected intervals along the SBK Line tunneling route as an instrumentation and control measure offer an opportunity to evaluate and back analyze the ground response due to tunneling works. This paper presents and discusses the volume loss caused by EPB TBM tunneling in the Kenny Hill Formation. Back analysis on trough width parameter from the available data has also been carried out. The findings of this study could be useful as a reference for future tunneling projects in similar ground conditions Â© Int. J. of GEOMATE. All rights reserved, including the making of copies unless permission is obtained from the copyright proprietors.